FEATURES OF USING DIGITAL TECHNOLOGIES IN THE TRAINING OF SKILLED WORKS (Innovative professional education, 2025)
The modern educational paradigm is actively addressing societal demands by integrating advanced technologies into the pedagogical framework. Among these, digital technologies are pivotal in enhancing the quality of educational delivery and fostering a conducive environment for active student engagement in cognitive processes. It is imperative to meticulously plan the integration of these technologies within the lesson structure. Digital technologies facilitate a learning environment that is mobile, differentiated, and tailored to individual learner needs.
Keywords: educational process, digital competence, digital technologies, educational services, learner, educational platforms, web resources, and there